First-principles prediction of two atomic-thin phosphorene allotropes with potentials for sun-light-driven water splitting. (7th January 2019) - Jiao, Na; Zhou, Pan; Xue, Lin; He, Chaoyu; Sun, Lizhong
Abstract: Based on first-principles, the structures, stabilities, electronic and optical properties of two new atomic-thin phosphorene allotropes, named as stair-P and zipper-P, are systematically investigated. Stair-P and zipper-P are constructed based on the previously proposed stair-graphane and zipper-graphane, respectively. They are confirmed to be dynamically stable phosphorene allotropes with energetic stabilities comparable to the experimentally synthesized black-P and blue-P. Stair-P and zipper-P are all semiconductors with indirect band gaps of 2.32 eV and 2.00 eV, respectively. These band gaps can be effectively modulated by in-layer compressive and stretching strains. The band edges of stair-P and zipper-P are proper for water splitting at both acidic (PH  =  0) and neutral (PH  =  7) environments and their sun-light adsorbing abilities are better than black-P and blue-P in the visible range.